Development of frozen green mango nectar - Tan, Mariquit B.; Guzman, Matilde P. (1990.)
ABSTRACT The development of frozen green mango nectar involved the determination of the best pulp to water ratio; selection of the most acceptable brix level; and identification of the most adequate processing method. In phase I, the three pulp (P) to water (W) ratio are 100P:50W, 100P:65W, and 100P:80W. The ratio of 100P:65W was found to produce a product of moderate thickness and light lemon yellow color. The brix level of the nectar was adjusted to 33° and 40° in Phase II. Both treatment gave a slightly thin consistency and dull yellow color, acceptability of the 40°Bx was slightly higher than the one with 33°Bx. Results of Phase III showed that pasteurization at 70°C for 30 seconds was more adequate in eliminating microorganisms than for 60°C at 6 minutes. However, the sweet-sour flavor of the unheated sample was more superior than the pasteurized ones. The sample heated at 70°C for 30 seconds was characterized as dull yellow in color, with moderately thin consistency and has "just recognizable" frozen green mango odor. As a juice drink, its acceptability level was "like slightly".
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Fruit -- Preservation; Mango